Tinjuauan Hukum Islam Terhadap Pengembangan Wisata Tumpak Lego Hill di Desa Krajan Kecamatan Ngrayun Kabupaten Ponorogo - Ulfiana Rofiqoh; Ahmad Syafi'i SJ; Khoirul Fathoni (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Indonesia is a very broad country. Each region has diverse and beautiful natural potentials and unique local culture. The beauty of nature and local culture is a great potential to be developed as a tourist attraction and managed as one of the community’s economic resources. In some ways, tourism also contributes to reducing poverty. Just like the tour that just opened in November 2023, namely the Tumpak Lego Hill tour which is located in Ngrayun Ponorogo. With the formulation of the problem as follows: 1) What is the process of developing Tumpak Lego Hill tourism in improving the economy of the people in the village of Krajan Ngrayun Ponorogo?; 2) How is the review of Islamic law related to the development of the Tumpak Lego hill tourism in improving the community’s economy in the village of Krajan Ngrayun Ponorogo?. The research method used in this research is field research with the aim of knowing the data directly. According to Bogdan and Taylor, qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. With data collection techniques consisting of: 1) observation; 2) interviews; 3) documentation. The results of the analysis show that 1) the tourism development process uses tourism product development, promotion development, spatial management, humam resource empowerment and environmental management. 2) the management of these tours is in accordance with maslahah dhoruriyyah with efforts to maintain environmental sustainability (hifzh al-bi’ah) and the existence of these tours has positive impacts such as employment, increasing people’s income and opening opportunities for people to develop Micro Enterprises, Small and Medium Enterprises (MSMEs).